Call it courage - Sperry, Armstrong 1897-1976 (New York Aladdin Books London Collier Macmillan, 1990)
Relates how Mafatu, a young Polynesian boy whose name means Stout Heart, overcomes his terrible fear of the sea and proves his courage to himself and his people
American Corner
winner of the newbery medal
11 13
Keywords: Courage -- Folklore; Folklore -- Polynesia; Survival -- Folklore